Multifunctional biomimetic LbL coatings that combine bioactivity with superior adhesion for orthopaedic applications - Rego, S. (2014)
In a marine environment, specific proteins are secreted by mussels and used as a bioglue to stick to a surface allowing generate irreversible bonding. Adhesive secreted proteins of mussels present an unusual amino acid 3,4-dihydroxyphenylalanine, DOPA [1]. The outstanding adhesive properties of these materials in the harsh conditions of the sea, impossible to mimic by human efforts until now, have been attributed to the presence of the catechol groups present in DOPA [2]. So, inspired by nature and in particular by the mussel adhesive proteins (MAPs), layer-by-layer films (LbL) with superior adhesive properties in wet environments were developed in this work. These LbL films were based on natural polymers combined with catechol groups, in particular hyaluronic acid and chitosan that have demonstrated adequate properties such as biocompatibility for several biomedical applications, in order to obtain films with enhanced tissue-adhesive properties and improved cell behaviour. Moreover, in order to develop truly multifunctional mussel inspired LbL films, bioactive nanoparticles were incorporated in their composition, besides the presence of the catechol groups. The final goal is to specifically use these films as coatings of a variety of implants for orthopaedic applications in order to improve both cell response and osteoconductivity in a simple and versatile way. Several techniques were used to characterize the properties of the developed films, such as UV spectrophotometry, quartz-crystal microbalance with dissipation monitoring (QCM-D), mechanical tests and SEM.